Target-directed development and preclinical characterization of the proposed biosimilar rituximab GP2013. Issue 7 (July 2014) - da Silva, Antonio; Kronthaler, Ulrich; Koppenburg, Vera; Fink, Martin; Meyer, Ines; Papandrikopoulou, Anastassia; Hofmann, Matthias; Stangler, Thomas; Visser, Jan
Abstract Biosimilar development involves a target-directed iterative process to ensure a similar product to the originator. Here we report the preclinical development of the proposed biosimilar rituximab (GP2013). Post-translational modifications and bioactivities of GP2013 versus originator rituximab were engineered and monitored to ensure similar pharmacological profiles. Antibody-dependent cellular cytotoxicity (ADCC) was used to illustrate how different glycosylation patterns and structure–function relationships were controlled during process development. Pharmacological comparability between GP2013 and originator rituximab were confirmed in preclinical studies using clinical scale drug product. Similar in vitro ADCC potency was demonstrated when compared in a dose–response manner against two lymphoma cell lines using freshly purified human natural killer (NK) cells. In vivo efficacy was demonstrated in two well characterized mouse xenograft models, testing at sensitive sub-therapeutic dose levels. Pharmacokinetics and pharmacodynamics (CD20 cell depletion) were likewise comparable in cynomolgus monkeys. This preclinical comparability exercise confirms that GP2013 and originator rituximab are pharmacologically similar.